Two-parametric beam model for dosimetry of the process of electron irradiation of materials with low density and atomic number - Lazurik, V.T.; Lazurik, V.M.; Popov, G.; Zimek, Z. (Вопросы атомной науки и техники, 2021)
The work is devoted to studying the possibility of using a two-parametric model of an electron beam to describe the depth distributions of the electron dose in materials with a low density and an effective atomic number. In this model, the parameters are determined by fitting the semi-empirical model (PFSEM-method) to the results of measurements of the depth-dose distribution in a dosimetric wedge. The depth-dose distributions in a birchwood wedge were measured at the Institute of Nuclear Chemistry and Technology in Warsaw, Poland. The parameters of the electron beam incident on the wedge were determined by the PFSEM method. The Monte Carlo simulations of the depth-dose distribution in the wedge for the process of electron irradiation, the characteristics of which are determined by the PFSEM method, have been carried out. It is shown that there is a satisfactory agreement between the measurement results and the Monte Carlo simulation of the depth-dose distribution. The advantages of describing depth-dose distributions in a wedge based on a two-parametric model of an electron beam in comparison with traditional methods of polynomial approximation of measurement results are discussed. Робота присвячена дослідженню можливості використання двопараметричної моделі електронного пучка для опису розподілу дози електронів по глибині в матеріалах з низькою щільністю і ефективним атомним номером. У цій моделі параметри визначаються шляхом підгонки напівемпіричної моделі (PFSEM-метод) до результатів вимірювань розподілу дози по глибині в дозиметричному клині. Розподіл дози по глибині в клині з березової деревини було виміряно в Інституті ядерної хімії та технологій в Варшаві, Польща. Параметри падаючого на клин електронного пучка визначалися методом PFSEM. Проведено моделювання методом Монте-Карло розподілу дози по глибині в клині для процесу електронного опромінення, характеристики якого визначені методом PFSEM. Показано, що існує згода між результатами вимірювань і моделюванням методом Монте-Карло розподілу дози по глибині. Обговорюються переваги опису розподілу дози по глибині в клині на основі двопараметричної моделі електронного пучка в порівнянні з традиційними методами поліноміальної апроксимації результатів вимірювань. Работа посвящена исследованию возможности использования двухпараметрической модели электронного пучка для описания распределения дозы электронов по глубине в материалах с низкой плотностью и эффективным атомным номером. В этой модели параметры определяются путем подгонки полуэмпирической модели (PFSEM-метод) к результатам измерений распределения дозы по глубине в дозиметрическом клине. Распределение дозы по глубине в клине из березовой древесины было измерено в Институте ядерной химии и технологий в Варшаве, Польша. Параметры падающего на клин электронного пучка определялись методом PFSEM. Проведено моделирование методом Монте-Карло распределения дозы по глубине в клине для процесса электронного облучения, характеристики которого определены методом PFSEM. Показано, что существует удовлетворительное согласие между результатами измерений и моделированием методом Монте-Карло распределения дозы по глубине. Обсуждаются преимущества описания распределения дозы по глубине в клине на основе двухпараметрической модели электронного пучка по сравнению с традиционными методами полиномиальной аппроксимации результатов измерений.